2019
DOI: 10.1101/531343
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mapping changes in the spatiotemporal distribution of lumpy skin disease virus

Abstract: 19Lumpy skin disease virus (LSDV) is an infectious disease of cattle transmitted by arthropod 20 vectors which results in substantial economic losses due to impact on production efficiency 21 and profitability, and represents an emerging threat to international trade of livestock 22 products and live animals. Since 2015, the disease has spread across many Eastern European 23 countries as well as Russia and Kazakhstan. This rapid expansion highlights the emergent 24 nature of the virus in more temperate regions… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 60 publications
(69 reference statements)
0
5
1
Order By: Relevance
“…Allepuz et al (2019) identified increased odds of LSDV associated with land cover (specifically, cropland, grassland or shrubland compared with forest), higher cattle densities, higher annual mean temperature and higher diurnal temperature ranges. By contrast, Machado et al (2019) did not identify any association between land cover and the risk of LSDV but did find an increased risk associated with higher temperatures, higher precipitation and lower wind speeds. Despite the differences in underlying risk factors, both studies identified similar regions as being at high risk of LSDV transmission.…”
Section: Risk Assessmentcontrasting
confidence: 60%
See 4 more Smart Citations
“…Allepuz et al (2019) identified increased odds of LSDV associated with land cover (specifically, cropland, grassland or shrubland compared with forest), higher cattle densities, higher annual mean temperature and higher diurnal temperature ranges. By contrast, Machado et al (2019) did not identify any association between land cover and the risk of LSDV but did find an increased risk associated with higher temperatures, higher precipitation and lower wind speeds. Despite the differences in underlying risk factors, both studies identified similar regions as being at high risk of LSDV transmission.…”
Section: Risk Assessmentcontrasting
confidence: 60%
“…By contrast, Machado et al. () did not identify any association between land cover and the risk of LSDV but did find an increased risk associated with higher temperatures, higher precipitation and lower wind speeds. Despite the differences in underlying risk factors, both studies identified similar regions as being at high risk of LSDV transmission.…”
Section: Assessmentmentioning
confidence: 88%
See 3 more Smart Citations